Talin‐driven inside‐out activation mechanism of platelet αIIbβ3 integrin probed by multimicrosecond, all‐atom molecular dynamics simulations. Issue 12 (25th September 2014) - Provasi, Davide; Negri, Ana; Coller, Barry S.; Filizola, Marta
ABSTRACT Platelet aggregation is the consequence of the binding of extracellular bivalent ligands such as fibrinogen and von Willebrand factor to the high affinity, active state of integrin αIIbβ3. This state is achieved through a so‐called "inside‐out" mechanism characterized by the membrane‐assisted formation of a complex between the F2 and F3 subdomains of intracellular protein talin and the integrin β3 tail. Here, we present the results of multi‐microsecond, all‐atom molecular dynamics simulations carried on the complete transmembrane (TM) and C‐terminal (CT) domains of αIIbβ3 integrin in an explicit lipid‐water environment, and in the presence or absence of the talin‐1 F2 and F3 subdomains. These large‐scale simulations provide unprecedented molecular‐level insights into the talin‐driven inside‐out activation of αIIbβ3 integrin. Specifically, they suggest a preferred conformation of the complete αIIbβ3 TM/CT domains in a lipid‐water environment, and testable hypotheses of key intermolecular interactions between αIIbβ3 integrin and the F2/F3 domains of talin‐1. Notably, not only do these simulations give support to a stable left‐handed reverse turn conformation of the αIIb juxtamembrane motif rather than a helical turn, but they raise the question as to whether TM helix separation is required for talin‐driven integrin activation. Proteins 2014; 82:3231–3240. © 2014 Wiley Periodicals, Inc.